Young practitioners' attention to health Qigong on video-based social media: a qualitative study of online Baduanjin learning - Chen, JiaBao; Zhang, YuSheng; Zhang, DeSheng (Frontiers in Communication, 2025)
IntroductionHealth Qigong is rooted in Chinese national culture, boasting a unique movement pattern and distinctive health-preserving value. Traditional national health Qigong, represented by Baduanjin, has attracted a large number of young practitioners. Against the backdrop of digital media, this study explores the motivation for young people's engagement with online Baduanjin, their emotional responses, and the subsequent behavioral paths of practice from a youth perspective, aiming to explain the reasons behind the “revival trend” of Baduanjin among young groups.MethodsBased on the Stimulus-Organism-Response (SOR) theoretical framework, this study adopts an inductive qualitative content analysis approach, focusing on young practitioners. Keywords were searched on Bilibili, a social media video platform, yielding 39,410 Baduanjin-related comments. Additionally, semi-structured interviews were conducted with 11 practitioners aged 18–28. The comments and interview data were coded separately for triangulation and presented jointly in the results section.ResultsBy collecting and analyzing Bilibili comments on Baduanjin videos and interview transcripts from practitioners, a theoretical model centered on the core category “young users' participation in online Baduanjin practice” was constructed. Practitioners' participation is mainly driven by two core dimensions: (1) Baduanjin content-related factors: perceived benefits, practicality and credibility, practice risks, and multi-dimensional comparison, which are partially associated with cultural familiarity; (2) Platform and external context-related factors: platform affordances, academic stress stimuli, celebrity influence, and social support. Emotional attitudes are formed after attempting practice and are positively correlated with practitioners' expectations of Baduanjin's effects. Subsequent practice behaviors exhibit three trajectories: sustained practice, abandonment, and resumption after suspension.ConclusionThis study argues that against the backdrop of social media platforms serving as a social infrastructure, young users' participation in online Baduanjin is a process jointly driven by content characteristics, platform cues, and contextual factors. Through changes in emotions and self-efficacy, this process ultimately leads to diverse participation behaviors. As a traditional national fitness activity with cultural resonance and social adaptability, Baduanjin provides valuable theoretical implications for promoting sustainable health behaviors among modern people. It can serve as a carrier of traditional Chinese “health-preserving” cultural knowledge, facilitating the effective dissemination of national fitness activities.